Mapping the variability of carbonation progress using GIS techniques and field data: a case study of the Limassol district - Tantele, Elia; Votsis, Renos; Danezis, Chris; Anastasiou, Constantina; Georgiou, Nikolas (My University, 2016)
Carbonation-induced corrosion of the steel reinforcement is the major deterioration factor of the RC infrastructures in urban areas. Carbonation progress in concrete is influenced by the exposure and environmental conditions prevailing at each area. Therefore, the rate of deterioration due to carbonation varies at different areas. Field measurements can quantify this carbonation progress for specific structures and areas. However, the scattered nature of individual field data offers little information to be considered for the assessment of existing structures or the design of new structures. This study aims to bridge this gap and shows that individual field data can be combined to characterise an area using GIS mapping tools. A generated map can depict the variability of carbonation progress with the geographical location. Measurements of the carbonation depth of several buildings at different locations in the Limassol district have been provided by a construction laboratory. Such information can be used to depict the carbonation progress on each structure through the calculation of the carbonation factor and then portray its value using mapping techniques. The result is a corrosion risk map of the Limassol district depicting the variability of carbonation progress with geographical locations. This can be used by engineers and managing authorities as a prediction tool for the initiation of carbonation-induced corrosion in existing structures and also at design stage to set the durability requirements of the concrete cover depth.
Keywords: Carbonation; Corrosion risk; Field measurements; GIS; RC buildings